Asociación entre los niveles de zinc intracelular y el estado nutricional de los niños infectados por el virus de la inmunodeficiencia humana y los niños expuestos al virus no infectados (2015)
ABSTRACT: Malnutrition, growth retardation and opportunistic infections outlast the metabolic, immune and gastrointestinal disorders produced by HIV. Zinc deficiency has been associated with deteriorating nutritional status, growth failure, and risk of infection. The aim of this study is to determine the association between zinc levels in peripheral blood mononuclear cells (PBMC) and the nutritional status of HIV-infected and uninfected children exposed to the virus. Patients and Methods: An analytical, observational, cross-sectional study was conducted on 17 infected and 17 exposed children, aged 2-10 years. Anthropometric measurements, clinical and nutritional history, 24 h recall, measurement of physical activity, and zinc in PBMC by fiow cytometry analysis were recorded. Results: Height according to age, energy consumption and adequacy of energy, protein and dietary zinc were significantly higher in children exposed to the virus compared to those infected with HIV (P < 0.05). No significant differences were found in BMI, levels of zinc in monocytes, CD4+ and CD4- lymphocytes between the two study groups (P > 0.05). However, the median levels of zinc in monocytes of infected patients was higher (218.6) compared to the control group (217.0). No association was found between zinc intake and levels of intracellular zinc. Conclusions: The deterioration of nutritional status and growth retardation in children were associated with HIV, but not with the levels of intracellular zinc. The dietary intake of this nutrient was not associated with levels of zinc in monocytes or CD4+ and CD4- lymphocytes.